Characterisation and Electron Paramagnetic Resonance Spectra of Some Copper(II) Complexes Derived from Heterocyclic Ligand 5,5´ -diethyl-2,4,6(1H)-Pyrimidinetrione and Amines - Narain, Gopal; K. Verma, Mahesh; Kumar Jain, Jai (Asian Journal of Chemistry, 2010)
Some tetracoordinated complexes of 5,5´-diethyl-2,4,6-(1H) pyrimidinetrione (barb) of copper(II) with amines have been prepared and characterised. The general molecular formula on the basis of analytical data is [Cu(barb)2(amine)]. The EPR data suggest monomeric nature of the complexes and very low exchange coupling. The infrared, magnetic and electronic data of the complexes are discussed in the light of the structures assigned.